Correlation between bibliometric indicators in Web of Science y Scopus journals - Salvador-Oliván, José Antonio; Agustín-Lacruz, Carmen (Revista General de Información y Documentación, 2015)
This article compares the correlation between bibliometric indicators obtained from journals indexed in the Web of Science (WoS) and Scopus databases in 2013. Indicators selected for analysis include impact factor (FI), 5-year impact factor (5yrFI), Inmediacy index, Eigenfactor Score (EF), Article Influence Score (AIS), SCImago Journal Rank (SJR), cites/docs 2 years (FIScopus), h-index, Impact Per publication (IPP) and Source Normalized Impact per Paper (SNIP). From 10700 journals listed in both databases, 9657 for analysis were selected because they contained all indicators. Correlations were determined for each pair of indicators and were tested with Spearman’s rho. The results shown that the correlations between several indicators are high and that they exhibit similar values in science and social sciences, providing evidence of convergent validity. Only H-index presented the lowest values providing complementary information to other indicators.